THE EFFECTIVENESS OF USING COMIC STRIPS TO STUDENTS ABILITY IN READING COMPREHENSION OF SPOOF TEXT AND STUDENTS’ MOTIVATION : EFEKTIVITAS PENGGUNAAN COMIC STRIP TERHADAP KEMAMPUAN SISWA DALAM PEMAHAMAN MEMBACA TEKS SPOOF DAN MOTIVASI SISWA - Ndruru, Hepilina (UPMI Proceeding Series, 2024)
The objective of this study is to find out whether COMIC STRIPS has significant effect COMIC STRIPS on the students’ Reading Comprehension of spoof text at the eight grade of SMP Parulian 3 Medan in academic year 2024/2025. The subject of the study was 47 students of the tenth grade students of SMP Parulian 3 Medan, which were chosen randomly. The writer took two groups of the students as the samples, one as the experimental group and another one as the control group. The data were collected by using reading test. The data were analyzed by t-test. The type of this research is an experimental research. The result of the study showed that the means of experimental group is 80,25 and it is good category. The means of the students who were taught reading comprehension of spoof text by using COMIC STRIPS technique was 80.25, the means of the students who were taught Reading Comprehension of spoof text without COMIC STRIPS technique is 67.75. It could be seen from the final result of t-test analysis which stated that the t-value was higher than the t-table (6.3549> 0,320). There was a difference in the students’ achievement in writing recount texts between students taught using COMIC STRIPS media and those without using COMIC STRIPS median. Having analyzed the data, the writer found that the students’ achievement of experiment class was better than that of the control class.